Bowman-stromal inlay using an intraocular lens injector for management of keratoconus. Issue 12 (December 2021) - Mittal, Vikas; Rathod, Darshana; Sehdev, Nancy
Abstract : The technique describes a simple approach to Bowman layer transplantation and stromal augmentation in patients with progressive keratoconus, which helped in stabilization of ectasia along with predictable increase in pachymetry. Abstract : A simple approach for transplanting Bowman layer and anterior stroma Bowman-stromal inlay (BSI) in keratoconic patients as an intervention to cease progression of ectasia and increase the overall thickness is described. A femtosecond laser was used to create BSI from human eye bank donor corneas and form an intrastromal pocket in the host cornea. The inlay was placed in the intrastromal space using an intraocular lens injector. This technique was performed successfully in 10 eyes of patients with progressive corneal ectasia. Postoperatively, the increased host pachymetry was as per BSI thickness. The tomography parameters remained stable, suggesting stabilization of keratoconus over a mean 15.9 months of follow-up. The BSI may offer a technically easy and safe technique of stromal augmentation to arrest keratoconus progression. It also opens up the possibility of surface ablation in the future for visual rehabilitation.